Prevalence and predictors of statin therapy in the general working-age population - V. S. Kaveshnikov; V. N. Serebryakova; I. A. Trubacheva (Российский кардиологический журнал)
Aim. To study the prevalence and predictors of statin therapy in the general working-age population.Materials and methods. As a part of the ESSE-RF study, we examined 1,600 people aged 25-64 years (women — 59%) from the general population. All subjects signed informed consent. Association analysis included blocks of socio-economic, psychosocial, behavioral, and medical variables. We used methods of univariate and multivariate statistics. Error probability < 5% was considered significant.Results. The prevalence of statin therapy in the general population was 3,3%: 5,5% in subjects ≥45 years, 8,1% in the group of 55-64 years old. We revealed that 2,5%, 2,9% and 10,9% of individuals with moderate, high and very high risk received statins, respectively. Among those receiving statins, 28,8% took it for primary prevention, 50% — due to cardiovascular diseases (CVD), and 21,2% — due to other disorders specifying risk. With priori indicators of very high risk, statins were taken more often than with SCORE ≥10 without risk indicators. According to multivariate model, older age, the presence of CVD + moderate and severe carotid atherosclerosis, antihypertensive therapy, stage 3 chronic kidney disease, and diabetes increased the likelihood of statin therapy, and SCORE ≥10 without risk indicators reduced it. The obtained data do not confirm the hypothesis about the significant role of sex, social gradient, and behavioral factors.Conclusion. Statins are one of the primary tools for primary and secondary prevention of CVD. Only a minor part of the population takes these drugs, in most cases due to CVD. Therefore, the prevention potential of statins at the population level has not yet been exhausted. More attention is required for individuals with SCORE ≥5 and without CVD who are less likely to receive therapy, but who may benefit more by taking statins. The decision to take statins for primary prevention of CVD should be based on the baseline risk, the value of absolute risk reduction, and how much this reduction justifies possible harm and long-term daily intake of the drug.